Form three students’ perception towards the use of communicative language games in Sekolah Menengah Kebangsaan Ajil, Hulu Terengganu / Ahmad Fuad Zakaria - Zakaria, Ahmad Fuad (2002)
This study is done with the purpose to investigate and to know the Form Three students’ perception towards the use of communicative language games in Sekolah Menengah Kebangsaan Ajil, Ajil, Hulu Terengganu. This study also examined the role of communicative language games in enhancing students’ interest in English language learning. It also examined to what extent that communicative language games motivate students in sustaining the interest of English language learning. In obtaining the data for this research, a study involving a questionnaire survey was conducted on 60 respondent. All the respondents are from the Form Three students of Sekolah Menengah Kebangsaan Ajil. All the responses were analyzed in term of means, percentages or frequencies of distribution among the variables used in the survey. Results of the analysis showed that communicative language games have great influenced in enhancing students’ interest towards English language learning. This study has proven that the present contemporary communicative approaches as advocated in the KBSM (Kurikulum Bersepadu Sekolah Menengah) English language syllabus is the most appropriate and applicable pedagogy catering for the need of secondary students in this particular school.